Safety and outcome of external beam radiation and neutron brachytherapy in elderly patients with esophageal squamous cell cancer - Li, Tao; Zhang, Wei; Lv, Jiahua; Liu, Huiming; Wang, Qifeng; Jia, Xitang; Liu, Bo; Lang, Jinyi (Journal of Contemporary Brachytherapy, 2017)
Purpose: The aim of this study was to retrospectively observe and analyze the long-term treatment outcomes of 191 elderly patients with esophageal squamous cell cancer (ESCC) who were treated with californium-252 (252Cf) neutron brachytherapy (NBT) in combination with external beam radiotherapy (EBRT). Material and methods : From January 2002 to November 2012, 191 patients with ESCC underwent NBT in combination with EBRT. The total radiation dose to the reference point via NBT was 8-25 Gy-eq in two to five fractions with one fraction per week. The total dose via EBRT was 50-60 Gy, which was delivered over a period of 5 to 6 weeks with normal fractionation. Results : The median survival time for the 191 patients was 23.6 months, and the 5-year rates for overall survival (OS) and local-regional control (LRC) were 28.7% and 54.2%, respectively. The patients’ age was a factor that was significantly associated with OS (p = 0.010), according to univariate analysis. The 5-year OS (LRC) was 37.3% (58.6%) for patients aged 70-74 years and 14.5% (47.9%) for patients aged > 74 years (p = 0.010 and p = 0.038). In multivariate analysis, age and clinical N stage were associated with OS and LRC (p = 0.011 [0.041] and p = 0.005 [0.005]). From the time of treatment completion to the development of local-regional recurrence or death, 5 (2.6%) patients experienced fistula and 15 (7.9%) experienced massive bleeding. The incidence of severe late complications was related to older age (p = 0.027), higher NBT dose/fraction (20-25 Gy/5 fractions), and higher total dose (> 66 Gy). Conclusions : The clinical data indicated that NBT in combination with EBRT produced favorable local control and long-term survival rates for elderly patients with ESCC, and that the side effects were tolerable. Patient’s age, clinical stage N status, and radiation dose could be used to select the appropriate treatment for elderly patients.